Structural and dielectric properties of boron doped and un-doped mullite thin films - Islam, Shumaila (2013)
A sol–gel technique being simple, low cost and application oriented has been used to synthesize doped and un-doped mullite sols. These films have been spin-coated onto copper substrates. Effect of boron doping on the transformation kinetics of mullite was studied by preparing two sols with ratio Al/Si/B = 3/1/0 and Al/Si/B = 3/1/0.5. Surface morphology of thermally stable films showed uniformity in doped and un-doped samples. X-ray diffractometer results revealed orthorhombic mullite formation from both sols at a temperature of 500 C for un-doped and at 350 C for doped mullite films. Small crystallite size *11 nm and low dielectric value *5.84 (at 3 MHz) were observed in boron-doped films. Un-doped mullite films also showed relatively low dielectric constant, *6.36, as compared to the previously reported values. The stoichiometry of films was confirmed by EDX and spark source mass spectrometry.